2021
DOI: 10.1172/jci.insight.148543
|View full text |Cite
|
Sign up to set email alerts
|

A potential pathogenic association between periodontal disease and Crohn’s disease

Abstract: Oral conditions are relatively common in patients with inflammatory bowel disease (IBD). However, the contribution of oral maladies to gut inflammation remains unexplored. Here, we investigated the effect of periodontitis on disease phenotypes of patients with IBD. In all, 60 patients with IBD (42 with ulcerative colitis [UC] and 18 with Crohn’s disease [CD]) and 45 healthy controls (HCs) without IBD were recruited for this clinical investigation. The effects of incipient periodontitis on the oral and gut micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 38 publications
2
40
1
Order By: Relevance
“… 5 , 17 20 Source Tracker analysis revealed that more oral-derived bacteria existed in the altered faecal samples of the SP group (Fig. 3f ), and Iima et al also revealed the similarity of the oral and gut microbiota, 21 supporting our hypothesis that the salivary microbiota of patients with periodontitis may induce gut microbiota dysbiosis by entering the gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 86%
“… 5 , 17 20 Source Tracker analysis revealed that more oral-derived bacteria existed in the altered faecal samples of the SP group (Fig. 3f ), and Iima et al also revealed the similarity of the oral and gut microbiota, 21 supporting our hypothesis that the salivary microbiota of patients with periodontitis may induce gut microbiota dysbiosis by entering the gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 86%
“…Inflammasome mutations can lead to inappropriate caspase-1 activation, which is associated with autoinflammatory syndromes [ 80 ]. Moreover, caspase-1 is involved in the pathogenesis of several diseases, including periodontal disease [ 4 ], Alzheimer’s disease [ 81 , 82 ], cardiovascular disease [ 83 ], rheumatoid arthritis [ 84 ], endometriosis [ 70 ], and Crohn’s disease [ 85 ], all of which are characterised by cell death and inflammation. Caspase-1 deficiency or inhibition protects against cell death, inflammation, and tissue dysfunction, associated with these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This can be noticed from the articles retrieved from the search strategy applied herein. It is also clear that other areas of medical knowledge besides dentistry focus on understanding pyroptosis-mediated inflammation processes [ 12 , 75 , 85 , 86 , 87 , 88 , 89 , 90 ]. Regarding periodontitis and periodontal therapies, the included articles present similarities regarding methods, type of cells involved, concentration, and kind of pyroptosis stimulation, as the outcomes point to the same direction considering the cellular events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that IBD patients display an increased prevalence of periodontitis [10, 11]. Also, early periodontitis may worsen clinical outcomes in some IBD patients [12]. Furthermore, the oral administration of P. gingivalis and F. nucleatum exacerbates the severity of dextran sulfate sodium (DSS)–induced colitis in mice by disrupting the intestinal barrier [1315].…”
Section: Introductionmentioning
confidence: 99%